Applying the Concept of an Entrepreneurship University: Princess Nourah Bent Abdul Rahman University as an Example - Alshiha, Adnan; Alrugabi, Nourah (The Arab Journal of Administration, 2023)
The aim of the research: to identify the degree of which Princess Nourah bint Abdul Rahman University is implementing of the dimensions of entrepreneur university according to the seven areas of the indicative framework issued in 2012 by the European Commission and the Economic Cooperation Organization, and to discuss the challenges the university faces in the process of becoming an entrepreneur university, and the requirements to overcome those challenges. Data and study sample: The field data was collected through a questionnaire prepared for this purpose and distributed to all university faculty members. 309 valid questionnaires were retrieved for analysis. The results of the study: The research reached a set of results, the most important of which are: the overall implementation of Princess Nourah Bint Abdul Rahman University of the dimensions of the entrepreneurial university, while the facing a medium degree of challenges as which encloud the followings: financial, Organizational, and expertise deficiency, technical impediment, and weak graduates. Conclusion: The research presented a number of recommendations, the most important of which are: establishing the entrepreneur professor’s laboratory, creating inspirational educational classes, encouraging university female employees to obtain the “International License for Entrepreneurship”, applying good governance standards to support the shift towards decentralization, adapting the regulations governing work to support entrepreneurial activities, increasing financial incentives for entrepreneurial activities, enhancing communication with local economic community.